Habitar fronteiras: transbordamentos da preceptoria nos processos de formação de Residências na Saúde Mental - Moura, Aline Silva de (2023)
The Multidisciplinary Residencies in Mental Health are training courses in/for the SUS (Unified Health System) that invest in proposing theoretical-practical experiences that allow residents to build meanings in the different scenarios of the Psychosocial Care Network. The preceptor, in this context, is linked to teaching and service institutions and has the obligation to directly monitor the practical activities carried out by residents in the field. The practice of preceptorship in health education, more specifically, in the practice scenarios of multidisciplinary residencies in mental health, is the object of this study. The overall objective is to analyze preceptorship practices in professional training processes in mental health, based on the experience of preceptors linked to Multiprofessional Residency Programs in Mental Health. As specific objectives we have: to characterize the professionals who act as preceptors in Multidisciplinary Residency programs in Mental Health; identify and analyze the educational strategies used for the practice of preceptorship and their articulations with public mental health policies; identify specificities, potentialities and challenges faced in training in mental health. We start from a research with a qualitative approach, taking cartography as a reference. The techniques used to record the data were: mapping of residency programs and literature; application of an online questionnaire (with the participation of 53 respondents) and the performance of a virtual group interview, with preceptors of mental health programs who participated in the stage of filling out the questionnaire (with the participation of 7 preceptors). Participants in both stages came from different locations and professional categories. The research diary was used as an instrument for recording and reflecting on the researcher. As a result, three dimensions emerged in the course of the research, addressing the inhabiting frontiers of/in the practice of preceptorship in mental health: 1) Inhabiting the world of work; where we will address the dimension of work in health and mental health care 2) Inhabit the world of education, where we will address the educational and pedagogical dimension of preceptorship and 3) Inhabit the world of residence, dimension in which we identify the emergence of practices of/in preceptorship, through the characters: preceptor-balancer; preceptor-intercessor and preceptor-cartographer. It is concluded that preceptorship in mental health, although it presents objective and subjective dimensions similar to preceptorship practices in different fields, retains specific aspects related to expanding the understanding of the health-disease-intervention process and focusing on critical and sensitive training in the field of health, madness, and society. Through pedagogical practices that consider these aspects, it is possible to strengthen care, interprofessional teamwork, and anti-asylum practices. The preceptors also recognized the importance of promoting care and attention to the mental health of residents during the training process, creating a supportive and welcoming environment. It is understood, therefore, that training in mental health care also implies training for self-care.